GEOMETRICAL STUDY OF SUSTAINABLE POLYMER PILES WITH BUCKLING ANALYSIS - Lee, Yee Yong; Ng, Chee Khoon; Lee, Yeong Huei; Ting, Sim Nee; Nicholas Kuan, Hoo Tien (Malaysia Institute of Planners, 2024)
Bakau piling is commonly used to support lightweight structures, such as drains, manholes, road, raft foundations and box culverts in construction, aside from its ability to sustain the deterioration of high-water table areas. Consequently, from the high demands, it is leading to mangrove deforestation. On the other hand, the alarming consent of environmental problems is that plastic products generated and becoming waste is increasing every year in Malaysia. Plastic products, mostly from polymer, require a long degradation period of about 1,000 years. Mangrove deforestation and the non-biodegradable nature of polymer waste have become environmental and global issues that leading to the innovative motive in this research by introducing polymer as a new material to the pile manufacturing, an alternative substitute for the bakau pile. This study aimed to optimise the polymer piles in relation to their structural behaviour under compressive stresses. Based on the developed numerical models, the optimum cross-sectional area of the polymer pile by using the buckling analysis is very much depending on the shape and size, specifically second moment of area and slenderness ratio. In preventing of torsional buckling, doubly symmetrical sections are the predominant consideration in the pile design. It found out that, the optimum polymer piles with 1.90 cm2 of crosssectional area could be suggested for H shape pile, and the proposed material is the high-density polyethylene (HDPE) with virgin to recycle ratio of 50% (VR 50). While serving the environmental issues of mangroves and waste management, polymer pile is a feasible alternative for sustainable construction.